2018
DOI: 10.1186/s12711-018-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in genome-wide and region-specific genetic diversity in the Dutch-Flemish Holstein–Friesian breeding program from 1986 to 2015

Abstract: BackgroundIn recent decades, Holstein–Friesian (HF) selection schemes have undergone profound changes, including the introduction of optimal contribution selection (OCS; around 2000), a major shift in breeding goal composition (around 2000) and the implementation of genomic selection (GS; around 2010). These changes are expected to have influenced genetic diversity trends. Our aim was to evaluate genome-wide and region-specific diversity in HF artificial insemination (AI) bulls in the Dutch-Flemish breeding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 63 publications
11
103
3
1
Order By: Relevance
“…However, lower intensity of selection in small 369 populations stems from fewer tested animals, and not more selected, which reduces a genetic pool 370 for selection. Our results are more in line with Doekes et al (2018). They attribute the higher rates 371 of inbreeding with genomic selection to the fact, that the animals with a higher relatedness to the 372 reference population have more accurate genomic predictions and are more likely to deviate 373 substantially and therefore to be selected (Habier et al, 2007;Clark et al, 2012).…”
Section: Loss Of Genetic Variation With Genomic Truncation Selection 356supporting
confidence: 58%
See 1 more Smart Citation
“…However, lower intensity of selection in small 369 populations stems from fewer tested animals, and not more selected, which reduces a genetic pool 370 for selection. Our results are more in line with Doekes et al (2018). They attribute the higher rates 371 of inbreeding with genomic selection to the fact, that the animals with a higher relatedness to the 372 reference population have more accurate genomic predictions and are more likely to deviate 373 substantially and therefore to be selected (Habier et al, 2007;Clark et al, 2012).…”
Section: Loss Of Genetic Variation With Genomic Truncation Selection 356supporting
confidence: 58%
“…The results have implications also for large populations, namely they show that genomic selection is 437 increasing turnover of germplasm per year with positive effect on genetic gain and negative effect 438 on genetic variation. This has been already indicated in real large populations (Doekes et al, 2018). 439…”
Section: Optimization Of Male Contributions Increased the Conversion supporting
confidence: 52%
“…Small population sizes in native breeds increase the risk on inbreeding and loss of genetic diversity through genetic drift [7]. Second, artificial selection, particularly in the Holstein Friesian breed, facilitated by techniques like artificial insemination and embryo transfer in combination with cryo storage, has further reduced genetic diversity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable concern on controlling inbreeding in cattle populations in the genomics era (Howard, Pryce, Baes, & Maltecca, ). Doekes, Veerkamp, Bijma, Hiemstra, and Windig () have investigated genetic diversity trends in the Dutch–Flemish Holstein–Friesian bull population, and reported that after the implementation of GS, inbreeding and kinship have increased substantially. Especially in small populations, the loss in genetic variance stands as an obstacle to improve genetic gains when performing genomic selection for many generations (Jannink, ).…”
Section: Discussionmentioning
confidence: 99%